1996
DOI: 10.1074/jbc.271.41.25369
|View full text |Cite
|
Sign up to set email alerts
|

The Antibiotic Bicyclomycin Affects the Secondary RNA Binding Site of Escherichia coli Transcription Termination Factor Rho

Abstract: The interaction of Rho and the antibiotic bicyclomycin was probed using in vitro transcription termination reactions, poly(C) binding assays, limited tryptic digestions, and the bicyclomycin inhibition kinetics of ATPase activity in the presence of poly(dC) and ribo(C) 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
123
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(131 citation statements)
references
References 46 publications
8
123
0
Order By: Relevance
“…4). Because inhibition of secondary-site RNA binding is indicative of bicyclomycin binding to Rho (26), these results strongly indicate that bicyclomycin is unable to bind to preclosed Rho rings. Thus, bicyclomycin appears to inhibit Rho by stabilizing a conformation that is incapable of ATP hydrolysis and is incompatible with stable RNA binding to its motor regions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…4). Because inhibition of secondary-site RNA binding is indicative of bicyclomycin binding to Rho (26), these results strongly indicate that bicyclomycin is unable to bind to preclosed Rho rings. Thus, bicyclomycin appears to inhibit Rho by stabilizing a conformation that is incapable of ATP hydrolysis and is incompatible with stable RNA binding to its motor regions.…”
Section: Discussionmentioning
confidence: 92%
“…S1) (24), is one such example. Previous studies have shown that bicyclomycin is a noncompetitive inhibitor of Rho ATPase activity and a mixed inhibitor of RNA binding to Rho's secondary site (25,26). Although subsequent structural studies suggested that bicyclomycin antagonizes Rho by sterically preventing the binding of the nucleophilic water molecule that initiates ATP hydrolysis (24), how bicyclomycin might interact with catalytically competent Rho states, such as those thought to accompany ATPase activity and translocation (17), has not been defined.…”
mentioning
confidence: 99%
“…3a). Growth of strains BSNusG3 and BSNusG4 in the presence of sufficient bicyclomycin to inhibit Rho-dependent termination (Magyar et al, 1996 ;Ingham et al, 1999) did not alleviate this apparent repression of Φ(nusG-lacZ) (Fig. 3a).…”
Section: Identification Of Rif R Mutations In the Rpob Gene Of B Submentioning
confidence: 95%
“…While Rho is essential for viability in many Gram-negative organisms, Gram-positive organisms appear to be less dependent on it, although it is important in preventing transcription of noncoding RNA in the latter and has activity against Micrococcus luteus (165,166). Bicyclomycin is the only known antibiotic to target Rho, and it does not affect RNA or ATP binding to Rho but does inhibit Rho-dependent transcription termination and ATP hydrolysis (167)(168)(169). Substitutions in E. coli Rho residues L208, M219, S266, and G337 conferred resistance to bicyclomycin, suggesting that Rho was the binding target of bicyclomycin (170,171).…”
Section: Termination Factor Rhomentioning
confidence: 99%